2018
DOI: 10.1016/j.solener.2017.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic analysis of solar stills using integrated fuzzy analytical hierarchy process and data envelopment analysis

Abstract: Desalination using solar stills is an ancient economic method for water desalination. Over the years, research and development in the area of solar still has resulted in increased distillate yield by means of integration of PCM (phase change material), photo-voltaic thermal (PVT), etc with the still. Nano-PCM is an upcoming technology which modifies the thermal performance of PCM. The aim of this research is to analyze the efficiency of 20 solar stills including nano-PCM based solar stills considering various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 78 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…The importance of solar stills is understood by utilizing a fuzzy analytical process to improve their productivity. Rufuss et al [14] suggested that the use of Fuzzy logic is beneficial in providing firm control over the temperature of the upper saline water of multi-stage desalination plants. The process was beneficial in providing input and output criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance of solar stills is understood by utilizing a fuzzy analytical process to improve their productivity. Rufuss et al [14] suggested that the use of Fuzzy logic is beneficial in providing firm control over the temperature of the upper saline water of multi-stage desalination plants. The process was beneficial in providing input and output criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This manuscript aims at identifying low-cost, durable, solar still materials to accomplish the eventual goal of producing and increasing accessibility of freshwater in small remote rural communities, especially in developing countries. A simple single basin solar still is considered for analysis in view of the increased complexity of stepped solar stills or solar still integrated with solar tracker (Dsilva Winfred Rufuss et al, 2018). The organization of the manuscript is as follows: firstly, low-cost, durable solar still materials with low embodied energy are identified from the literature based on the component requirements.…”
Section: Nomenclaturementioning
confidence: 99%
“…Even after complex calculations, fuzzy AHP is able to deal with the general appraisal of ambiguity because of human tendency [47]. e advantage of fuzzy logic is much accurate computation of the factors prioritizing and hierarchy creation [48]. Popular technique, fuzzified analytical hierarchical process is capable of solving the complicated problems Computational Intelligence and Neuroscience related to selection of vendors [49].…”
Section: Fuzzy Ahpmentioning
confidence: 99%